Modular multilevel converter for enhanced offshore windfarm integration to medium voltage DC microgrid - Lekshmi Babu; Mariamma Chacko (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2025)
The quality of power converters is crucial in integrating renewable energy sources into DC microgrids, as it ensures efficient energy transfer, voltage stability, and overall system reliability, making it a key focus of current research. This paper presents an application of enhanced Modular Multilevel Converter (MMC) proposed by the authors for integrating a Wind Energy Conversion System (WECS) into a Medium Voltage Direct Current (MVDC) microgrid. The system architecture involves a wind farm model connected to an MVDC grid via the MMC, with an Energy Storage System (ESS) integrated to support grid stability and manage energy flow. The key application of this configuration is to supply power to heavy-duty electric vehicles, such as electric trucks, making the system well-suited for industrial-scale electrification. The entire setup is simulated using MATLAB/SIMULINK to analyse its performance. The simulation results show several key improvements compared to MMC with conventional sorting algorithm. These include enhanced output DC voltage quality, faster short circuit fault clearing, better voltage balance across submodule capacitors, less Total Harmonic Distortion (THD) and reduced switching losses in the converter. These improvements make the proposed system highly efficient and reliable for modern renewable energy integration into MVDC microgrids, supporting the transition towards electric heavy vehicles while maintaining grid stability and efficiency.